Flammable material : German chemical workers in war, revolution, and inflation. 1914 - 1924 - Patton, Craig D. (Berlin, 1998)
"Patton's study of chemical workers in the decade 1914-1924 is a clarifying addition to German labor history. The author combines attention to detail with economic and political perspectives to achieve a nuanced interpretation of war, revolution, inflation, and the dynamics of collective action. Patton argues that labor protest in the chemical industry was directly linked to specific grievances that affected labor militancy, class solidarity, and political radicalism. Politicization of working conditions and economic distress formed a more powerful provocation for radicalization than ideological visions of a restructured society. This study brings the reader to the factory floor, where workers faced extraordinary demands and pressures that drove them to spontaneous action. Although Patton stresses specificity and immediateness, his analysis shows the interconnections among labor, the trade unions, and political parties. In order to understand class consciousness, solidarity, militancy, and radicalization, the author addresses those elements that both encouraged and limited collective action within the reality and rhetoric of massive dislocations and rising expectations."